Case Report: Drug-coated balloon after intravascular lithotripsy for the treatment of severely calcified de novo coronary artery lesion - Misawa, Toru; Lee, Tetsumin; Ashikaga, Takashi; Nozato, Toshihiro; Yonetsu, Taishi; Sasano, Tetsuo (Frontiers in Cardiovascular Medicine, 2024)
In patients undergoing percutaneous coronary intervention (PCI), severely calcified lesions remain a great challenge even in the drug-eluting stent (DES) era. Intravascular lithotripsy (IVL) is effective for modification of severely calcified lesions prior to DES implantation. However, the efficacy of PCI with drug-coated balloon (DCB) following IVL has not been fully elucidated. Here, we present a case of severely calcified de novo coronary artery lesion successfully underwent PCI with DCB following IVL under optical coherence tomography (OCT) guidance as well as mid-term follow-up OCT. DCB following IVL might be a potential revascularization strategy for patients with heavily calcified de novo coronary artery lesions.